TINGKAT KECUKUPAN ZAT GIZI, AKTIVITAS FISIK, DAN KEBUGARAN KARDIORESPIRATORI PEGAWAI PT. INDOCEMENT BOGOR - Tamimi, Kharisma; Rimbawan, Rimbawan (Jurnal Gizi dan Pangan, 2015)
ABSTRACTThe general objective of this study was to analyse nutritional adequacy, physical activity, and cardiorespiratory fitness among Indocement’s workers at Bogor. The cross-sectional study was applied with purposive sampling, involving 32 office workers and 32 plant workers. Most of subjects (59.4% and 78.2%) had a normal Body Mass Index (BMI). The mean VO2 max of plant workers (24.4±7.6 mL/kg/mnt) was higher than office workers (22.9±7.5 mL/kg/mnt). There were no differences of macrocutrients adequacy (energy, protein, fat, and carbohydrate) between two workers (p>0.05). Physical activity level of plant workers was higher than the office workers, and it was categorized as moderately active (59.4%), whereas the office workers categorized as sedentary (75.0%). The office workers had better exercise (160.3±118.0 minutes) than the plant workers (89.1±167.6 minutes). Moreover, there were differences on physical activity and habitual exercise between the two groups (p<0.05). The significant correlations between age, physical activity, and habitual exercise with VO2 max were found on plant workers (p<0.05), but not on office workers (p>0.05).Keywords: cardiorespiratory fitness, nutritional adequacy, physical activityABSTRAKTujuan penelitian ini adalah untuk menganalisis tingkat kecukupan gizi, aktivitas fisik, dan tingkat kebugaran kardiorespiratori pegawai PT. Indocement di Bogor. Desain penelitian adalah cross-sectional dengan purposive sampling, melibatkan 32 pegawai kantor dan 32 pegawai lapang PT. Indocement. Sebanyak 59,4% pegawai kantor dan 78,2% pegawai lapang memiliki IMT yang normal. Rata-rata VO2 max kelompok lapang (24,4±7,6 mL/kg/menit) lebih tinggi dibandingkan kelompok kantor (22,9±7,5 mL/kg/menit). Tingkat kecukupan zat gizi kedua kelompok tidak berbeda (p>0,05). Sebagian besar (59,4%) pegawai kelompok lapang mempunyai kategori aktivitas sedang dan sebanyak 75,0% kelompok kantor mempunyai kategori aktivitas fisik ringan. Kebiasaan olahraga kelompok kantor lebih baik (160,3±118,0 menit) dibandingkan kelompok lapang (89,1±167,6 menit). Terdapat perbedaan aktivitas fisik dan kebiasaan olahraga antara kelompok kantor dan lapang (p<0,05). Terdapat hubungan yang signifikan antara usia, kebiasaan olahraga, dan aktivitas fisik dengan VO2 max pada kelompok lapang (p<0,05), dan tidak terdapat hubungan pada kelompok kantor (p>0,05).Kata kunci: aktivitas fisik, kebugaran kardiorespiratori, tingkat kecukupan zat gizi